Flexible technologies of the reconfigurable automatic plants - Gurjanov, A V; Shukalov, A V; Zakoldaev, D A; Zharinov, I O (Journal of physics. Conference series, 2020)
The scientific problem is to analyze and to synthesize modern plants resource, which manufacture the devices in engineering. There is an analysis and scheme of plants resources in the existing enterprises, which use the flexible technologies of computer numerical control as a base for devices manufacturing. Obviously that computer numerical control robotic cell potential today has run out its possibility. There is an analysis and some ready theoretical solutions (scheme) in the subject area of the new paradigm reconfigurable manufacturing resource. Obviously that synthesis of new reconfigurable plant is based on flexible assembly technologies, which have some application for the industrial reconfigurable manufacturing systems. Reconfigurable manufacturing infrastructure elements of the existing enterprises and the modern plant are defined as well as new robots specialized for the reconfigurable automation plant.